Penerapan Metode Certainty Factor Dalam Mendiagnosa Penyakit PES - Rima Tamara Aldisa (Journal of Computer System and Informatics (JoSYC), 2023)
Plague is the oldest plague known to mankind and will continue to plague the world. Black Death is an infectious disease caused by the bite of Yersinia pestis, which breeds on rats. Human-to-human transmission occurs through droplets containing bubonic plague. Expert systems are a branch of artificial intelligence and a branch of knowledge that emerged with the development of computer science today. In this study, the expert system was implemented as a system for information or output to pursue certainty in diagnosing the type of bubonic plague felt by the patient based on the symptoms felt by the patient. Its use on the user's system must be combined with methods so that it runs correctly and optimally. In this study, the authors used the certainty factor (CF) method. CF is the internalization of uncertainty in professional thinking proposed by Shortliffe and Buchanan in 1975. Based on the results of the computational process using the CF method, information is generated that the patient suffers from multiple symptoms of bubonic plague, and the patient is diagnosed with pneumonic plague (P3) with an expression confidence level of 0.993 or 9.93%.